Carl Gustav Jung et les Noces Chymiques - Véronique Liard (Recherches Germaniques)
Two dreams had prefigured C.G. Jung's encounter with alchemy, but it is actually the Mystery of the Golden Flower that first led him to analyze the peculiarities of alchemy more closely. Soon enough, he noted that analytical psychology and alchemy overlapped. After studying the lifelong relation between Jung and alchemy, the present article focuses on the parallels that can be drawn between the different steps of alchemy and individuation. Then, we discuss the similarities and differences between Christian opus and alchemical opus. While the Christians expect divine grace through external influence, the alchemist seeks to accomplish the redeeming work by himself. To conclude, we will raise the question as to why Jung did not dedicate an entire book to the Chymical Wedding, though he regularly quoted parts of it and praised its importance.